Engaging Africa Washington and the fall of Portugal's colonial empire - Schneidman, Witney (Dallas University Press of America, 2004)
Engaging Africa: Washington and the Fall of Portugal's Colonial Empire tells the story of how successive administrations―Kennedy, Johnson, Nixon and Ford―tried to maintain the confidence of their NATO ally, Portugal, while facilitating the process of decolonization in Angola and Mozambique. Ultimately becoming an epic battle of democracy versus dictatorship, African nationalism versus geo-strategic pre-eminence, and East versus West, this book, largely based on primary sources, tells the story of one of the Cold War's most intense confrontations.
Includes index
Keywords: Africa